The incidence of venous thromboembolism in total joint replacement during COVID-19 pandemic: has lockdown had an influence?. (1st December 2020) - Khan, Shehzaad A.; Logan, Peter; Asokan, Ajay; Handford, Charles; Rajgor, Harshadkumar Dhirajlal; Khadabadi, Nikhil Aravind; Moores, Thomas; Targett, John
Abstract : Aims: As the first wave of the COVID-19 pandemic began to dip, restarting elective orthopaedics became a challenge. Protocols including surgery at 'green' sites, self-isolation for 14 days, and COVID-19 testing were developed to minimize the risk of transmission. In this study, we look at risk effects of 14-day self-isolation on the incidence of venous thromboembolism (VTE) in our green site hospital among patients undergoing total joint replacement (TJR). Methods: This retrospective cohort study included 50 patients who underwent TJR. Basic demographic data was collected including, age, sex, American Society of Anesthesiologists (ASA) grade, body mass index (BMI), type of surgery, and complications at two and four weeks. Univariate and multivariate analysis were used to identify risk factors associated with an increased risk of VTE. Results: A total of 50 patients were included in our study, with 24 males and 26 females. The mean age was 67.86 (SD 11.803). Overall, 8% of patients suffered a VTE complication; symptomatic non-fatal pulmoary embolism was confirmed in 6% of patients (n = 3) as an inpatient, and symptomatic deep vein thrombosis was diagnosed in 2% of patients (n = 1) within two weeks of their operation. All patients were found to be female (p < 0.001), had a BMI > 30 (p = 0.317), and were immobile prior to their operation using walking aids (p = 0.016). Conclusion: The incidence we report is much higher than the reported incidence in the literature, which we believe is related to the 14-day self-isolation period and immobility prior to their operation. We recommend that all patients undergoing TJR that require a period of self-isolation, are pre-assessed prior to self-isolation for their risk of VTE, potentially using mechanical and chemical prophylaxis to reduce the likelihood of developing VTE. Cite this article: Bone Jt Open 2020;1-12:751–756.